Exploring the Challenges Faced by Small Insurance Brokers in Achieving Sustainable Growth: A Case Study in Botswana's Insurance Industry - Malambo, Maalila (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study assesses the challenges faced by small insurance brokers in Botswana, focusing on regulatory dynamics, market conditions, financial constraints, technological disparities, consumer preferences, marketing limitations, distribution challenges, service constraints, and training needs. Design/methodology/approach: An online questionnaire was distributed to 50 small insurance brokers in Botswana, with a response rate of 70%. Semi-structured interviews were conducted with 10 key stakeholders, including regulators and customers, to gain deeper insights. Findings: The findings highlight significant barriers such as complex regulatory procedures, limited access to capital, technological challenges, consumer biases towards larger firms, and inadequate marketing and distribution channels. Research limitations/implications: The study's limitations include a focus on a specific geographic region and the reliance on self-reported data, which may introduce biases. Practical implications: The study underscores the need for streamlined regulatory processes, innovative financial solutions, digital transformation, customer-centric strategies, and strategic partnerships. Originality/value: This paper provides actionable insights for stakeholders to support the sustainable growth of small insurance brokers in Botswana, fostering a more inclusive and robust insurance sector.